UPAYA MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK TEMA 7 SUBTEMA 3 INDAHNYA PERSATUAN DAN KESATUAN NEGERIKU DI SD KELAS IV 100670 HUTAIMBARU - siti patimah harahap; Samakmur Samakmur; Monica Theresia (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2023)
Abstract This study aims to determine the use of the Talking stick model on students in class IV SD Negeri 100670 Hutaimbaru on 7 subtheme 3 themes. This type of research uses CAR (Classroom Action Research). The subjects in this study were all fourth grade students at SD Negeri 100670 Hutaimbaru which opened 20 people while the object of this research was the improvement of student learning outcomes on theme 7 sub-theme 3. The data collection techniques used was observation and tests. The results of my cycle show the results of observations from learning activities of 67.30% (less category) and the average student learning outcomes are 66.8 where 3 students (15%) are complete and 17 students (85%) are not. . Furthermore, the second cycle showed the results of observations from learning activities of 75% (enough categories) and an average of 78.2 where 11 students (55%) completed and 9 students (45%) did not complete. In conclusion, student learning outcomes in theme 7 sub-theme 3 can be improved by using the Talking stick model for fourth grade students at SD Negeri 100670 Hutaimbaru. Keywords: Improving Learning Outcomes, Talking Stick Model